Hubungan antara Status Gizi Awal dengan Status Pulang dan Lama Rawat Inap Pasien Dewasa di Rumah Sakit - Nurul Huda Syamsiatun; Hamam Hadi; Muhammad Juffrie (Jurnal Gizi Klinik Indonesia, 2004)
Background: Hospital malnutrition is reported to be prevalent in Indonesia. Wether nutritional status at admission is associated with nutritional status at discharge and length of stay remains unclear.Objective: To assess the association between nutritional status at the admission and nutritional status at discharge and length of stay in adult hospitalized patients.Methods: A total subjects of 293 adult patients who were admitted to internal and neurology departments of Dr. Sardjito, Dr.M.Jamil, and Sanglah hospitals were included in this study. Nutritional status of each patient was assessed using Body Mass Index (BMI) measured at admission and on discharge. Information on length of stay and hospital charge was collected based on medical records.Results: Low energy intake was associated with worse outcome (OR 1,2 95%CI 1,74-11,94). Non infection diseases were also found to be associated with worse outcome (OR 6,91 95%CI 4,03-11,85) and length of stay (OR 1,83 95%CI 1,10-3,05). Prehospitalized and class of hospitalized were associated with length of stay (OR 2,34 95%CI 1,36-8,57).Conclusion: Low nutritional status on admission and low energy intake were associated with higher risk of worse outcome (OR 2,34 95%CI 1,05-5,24) and (OR 3,41 95%CI 1,36-8,57).